AB0334 Knee function after total knee arthroplasty is influenced by disease activity in patients with rheumatoid arthritis. (15th June 2017) - Harigane, K; Kumagai, K; Mochida, Y; Ishii, K; Miyamae, Y; Choe, H; Nagaoka, A; Inaba, Y; Mitsugi, N; Saito, T
Abstract : Background: Several studies reported that development of phaemacological treatment for rheumatoid arthritis (RA) contributed to decreased number of orthopaedic surgery. [1–3] Surgical treatment is, however, still required in many cases, and the impact of orthopaedic surgery on disease activity remain unclear. Objectives: The aims of current study was to evaluate the effect of total knee arthroplasty (TKA) with capsulosynovectomy on changes of disease activity and knee function after TKA in patients with RA. Methods: Seventy-seven serial patients with RA (61 female and 16 male) who underwent primary TKA with more than one year of follow-up were retrospectively reviewed to assess postoperative disease activity and knee function. The mean age at the time of surgery was 68.3 years old. The disease activity of RA was measured using Disease Activity Score in 28 Joints (DAS28). Clinical outcome was measured by treatment score for RA knee of the Japanese Orthopaedic Association (JOA) score. To evaluate the effects of disease activity on knee function, outcomes at before and one year after surgery were separately investigated following two groups; patients who had remission or low disease activity in DAS28-CRP (good controlled group), and patients who had moderate or high disease activity (poor controlled group) one year after surgery. Results: The disease activity of RA was significantly decreased in DAS28-CRP one year after surgery. (3.9 vs. 2.7, p<0.01) Postoperative knee function was significantly improved in JOA scores one year after surgery. (48.9 vs. 86.0, p<0.01) As for differences of knee function between good and poor controlled group, the mean JOA score in good controlled group was significantly better than in poor controlled group. (90.4 vs. 82.1, p<0.01) Postoperative knee function was negatively correlated with RA disease activity. (R 2 =0.21, p<0.01) Conclusions: TKA with capsulosynovectomy improves both knee function and disease activity in patients with RA. Based on the results, knee function after TKA is influenced with disease activity. References: Dusad A et al. Impact of Total Knee Arthroplasty as Assessed Using Patient-Reported Pain and Health-Related Quality of Life Indices: Rheumatoid Arthritis Versus Osteoarthritis. Arthritis Rheumatol. 2015; 67: 2503–11. Yano K et al. Effect of total knee arthroplasty on disease activity in patients with established rheumatoid arthritis: 3-year follow-up results of combined medical therapy and surgical intervention. Mod Rheumatol. 2010; 20: 452–7. Oh K et al. Effects of surgical intervention on disease activity of rheumatoid arthritis: cases of surgery for rheumatoid arthritis of the lower limbs treated with biologics. Mod Rheumatol. 2014; 24: 606–11. Disclosure of Interest: None declared